An assessment of the longevity of samarium cobalt trioxide perovskite catalyst during the conversion of greenhouse gases into syngas - Osazuwa, Osarieme U.; Khan, Maksudur R.; Lam, Su Shiung; Assabumrungrat, Suttichai; Cheng, C. K. (Elsevier Ltd, 2018)
Catalytic carbon dioxide (CO 2) reforming of methane (CH4) has gained interest because it reduces the amount of greenhouse gases in the environment. In addition, the products from the reforming process are utilized as feedstock in the Fischer-Tropsch synthesis. However, rapid catalyst deactivation and sintering due to carbon deposition often accompany the CO2 reforming of CH4 reaction. In this study, samarium cobalt trioxides perovskite catalyst was synthesized and employed as catalyst in a 72 h longevity test conducted at 1073 K using CO2 to reform CH4 with gas-hourly-space velocity of 30,000 h− 1. Feed ratios (0.5–2.0) were varied and excellent catalytic longevity, maximum conversion (above 90%) and yield (above 60%), were obtained at 1.0 feed ratio.